Effective ?-radiation Dose on Chitosan for Preservation of Mangoes (Mangifera indica) - Islam, Ashna; Sultana, Mahfuza Sharifa; Parvin, Fahmida; Khan, Mubarak A (Jahangirnagar University Environmental Bulletin, 2013)
The effective dose of ? radiation on chitosan for mango preservation was studies in this work. The 2% chitosan solution was irradiated with at various total doses (50-200 kGy). The mature green mangoes were soaked in un-irradiated and irradiated chitosan solutions and then they were stored at normal room temperature. The percentage of weight loss, color change and percentage of spoilage were observed for 15 days in control, un-irradiated and irradiated chitosan coated mangoes. The overall results showed the superiority of 50 kGy and 100 kGy irradiated chitosan in extending shelf life of mango as comared to control, un-irradiated and 120 kGy to 200 kGy irradiated chitosan. Jahangirnagar University Environmental Bulletin, Vol.2, 35-40, 2013 DOI: http://dx.doi.org/10.3329/jueb.v2i0.16328